2009
DOI: 10.14430/arctic134
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary (1951–2001) Evolution of Lakes in the Old Crow Basin, Northern Yukon, Canada: Remote Sensing, Numerical Modeling, and Stable Isotope Analysis

Abstract: this study reports on changes in the distribution, surface area, and modern water balance of lakes and ponds located in the Old Crow Basin, northern Yukon, over a 50-year period (1951 -2001), using aerial photographs, satellite imagery, a numerical lake model, and stable O-H isotope analysis. Results from the analysis of historical air photos (1951 and 1972) and a Landsat-7 Enhanced thematic Mapper (EtM+) image (2001) show an overall decrease (-3.5%) in lake surface area between 1951 and 2001. Large lakes typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 39 publications
4
104
0
Order By: Relevance
“…For millennia, the Vuntut Gwitchin relied on the diverse network of lakes in OCF, which support waterfowl, fish, and other wildlife (Old Crow Flats Van Tat K'atr'anahtii Special Management Area Management Plan 2006). Lake drainage events are common in OCF (Labrecque et al 2009), and a recent remote sensing analysis identified that their frequency has increased markedly from 0.36 to 2.02 lakes · year -1 · 10 000 km -2 between 1950 and 2009, consistent with local observations of reduced water levels (Lantz and Turner 2015). The majority of lake drainage events in OCF are partial, leaving behind numerous residual waterbodies within the former lake basin (Lantz and Turner 2015).…”
Section: Introductionmentioning
confidence: 53%
“…For millennia, the Vuntut Gwitchin relied on the diverse network of lakes in OCF, which support waterfowl, fish, and other wildlife (Old Crow Flats Van Tat K'atr'anahtii Special Management Area Management Plan 2006). Lake drainage events are common in OCF (Labrecque et al 2009), and a recent remote sensing analysis identified that their frequency has increased markedly from 0.36 to 2.02 lakes · year -1 · 10 000 km -2 between 1950 and 2009, consistent with local observations of reduced water levels (Lantz and Turner 2015). The majority of lake drainage events in OCF are partial, leaving behind numerous residual waterbodies within the former lake basin (Lantz and Turner 2015).…”
Section: Introductionmentioning
confidence: 53%
“…Studies have also used surface areas smaller than 5.0×10 4 m 2 (Labrecque et al, 2009) or 1.0×10 4 m 2 (Rautio et al, 2011) to distinguish ponds from lakes.…”
Section: Definition Of Ponds and Lakesmentioning
confidence: 99%
“…A similar decline in lake area and abundance has occurred in northern Siberia since 1973 owing to subsurface drainage through discontinuous permafrost (Smith et al 2005). Labreque et al (2009) observed a reduction in lake surface area at a study site in the northern Yukon Territory, Canada, since 1951. The lakes experienced a water deficit that is attributed to a warmer climate and less precipitation.…”
Section: Temporal Variability In Polygon Pondsmentioning
confidence: 60%